Topologies of innovation networks in knowledge-intensive sectors: Sectoral differences in the access to knowledge and complementary assets through formal and informal ties - Salavisa, I. (2014)
This paper contributes to a better understanding of the sources of networking variety in knowledge-intensive sectors, focusing on molecular biotechnology and software for telecommunications. These sectors differ in the nature of the knowledge exploited and in the organisation of the innovation processes. Our argument is that the sectoral differences affect the type, the sources and the modes of access to resources necessary for innovation and therefore firms’ networking behaviour. The empirical research was based on extensive interviews with the entrepreneurs of 46 young firms of the two sectors in Portugal, complemented with documentary data. Networks were reconstructed and social network analysis was applied, distinguishing between the formal and informal relationships established to access both knowledge and complementary assets. The results show differences in the topology of networks within and across sectors, providing support to our argument. The differences become particularly evident regarding: i) the formal access to complementary assets, reflecting distinct dynamics of the environment where firms pursue their activities; ii) the informal access to knowledge, associated with differences in knowledge bases. The comparative approach permitted to obtain a more comprehensive picture of firms’ networking activities and a deeper understanding of the mechanisms behind the distinct sectoral network topologies.